Kulit ikan kakap tersamak: Exotic dan prospektif - Kasmudjiastuti, Emiliana (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2005)
Kakap fish skins are waste products of fillet industry. Up to now they have been wasted, of course accumulatively will cause environmental pollution. They are classified as the type of non conventional leather and exotic ones for the reasons of having special, beautiful, unique, typical, and attractive grain. Kakap fish skin have relatively small dimentions, there fore the tanning process can be done by home industry because simple equipments are possible to be used to process the fish skins into leather. In addition, Kakap fish leather have physical property of good tensile strength that may be used as material for leather goods. Although small however the exotic leather of kakap fish skins are prospective to be developed as material to manufacture exclusive leather goods, especially for niche markets. They also can be used as an alternative to substitute conventional leather. Keywords : kakap fish, waste, leather goods, exotic. ABSTRAK Kulit ikan kakap merupaan limbah dari industry fillet ikan, sementara ini hanya dibuang saja, sehingga makin menumpuk dn dapat menyebabkan pencemaran lingkungan. Kulit ikan kakap merupakan jenis kulit non konvensional dan dapat pula digolongkan sebagai kulit exotic karena memiliki rajah yang khas, indah, dan menarik. Kulit ikan kakap memiliki ukuran yang relatif kecil sehingga dalam proses penyamakannya cukup menggunakan peralatan yang sederhana dan dapat dikerjakan oleh industri rumah tangga. Disamping itu kulit, kulit ikan kakap yang exotic walaupun ukurannya kecil, prospektif untuk dikembangkan sebagai bahan baku untuk pembuatan barang-barang kulit yang eksklusif terutama untuk pasar khusus dan dapat digunakan sebagai alternative untuk menggantikan bahan kulit konvensional disaat kurangnya penyediaan kulit konvensional. Kata Kunci : ikan kakap, limbah, barang kulit, exotic.